Antiviral potential of natural compounds against influenza virus hemagglutinin. (December 2017) - Kannan, S.; Kolandaivel, P.
Graphical abstract: The antiviral activity of natural compounds against the HA protein of different subtypes of Influenza virus has been investigated using binding free energy and hydrogen bonding interactions. Highlights: The curucmin derivatives (CI, CII and CIII) found to posses higher binding affinity for H1, H2, H3 and H5 subtypes of influenza virus than other compounds. The binding capability of protein subtypes with curcumin derivatives and the binding affinity of curcumin compounds are in the order H1 > H2 > H3 and CI > CII > CIII respectively. The two -O-CH3- groups present in the CI compound help to have strong binding with HA protein than CII and CIII. The van der Waals interaction energy plays a significant role for binding in all the complexes. The conserved region (153–155) and the helix region (193–194) of H1, H2, H3 protein subtypes are found to possess higher binding susceptibility for binding of the curcumin derivatives. Abstract: Influenza virus of different subtypes H1N1, H2N2, H3N2 and H5N1 cause many human pandemic deaths and threatening the people worldwide. The Hemagglutinin (HA) protein mediates viral attachment to host receptors act as an attractive target. The sixteen natural compounds have been chosen to target the HA protein. Molecular docking studies have been performed to find binding affinity of the compounds. Out of the sixteen, three compounds CI, CII and CIII found to posses a higher binding affinity. The molecular dynamics (MD) simulation has been performed to study the structural, dynamical properties for the nine different complexes CI, CII, CIII bound with H1, H2, H3 proteins and the results were compared. The molecular mechanics Poission-Boltzmann surface area (MM-PBSA) method is used to compare the binding free energy, its different energy components and per residue binding contribution. The H1 subtype shows higher binding preference for all the curcumin derivatives than H2 and H3. The binding capability of protein subtypes with curcumin derivatives and the binding affinity of curcumin compounds are in the order H1 > H2 > H3 and CI > CII > CIII respectively. The two -O-CH3- groups present in the CI compound help to have strong binding with HA protein than CII and CIII. The van der Waals interaction energy plays a significant role for binding in all the complexes. The hydrogen bonding interactions were monitored throughout the MD simulation. The conserved region (153–155) and the helix region (193–194) of H1, H2, H3 protein subtypes are found to possess higher binding susceptibility for binding of the curcumin derivatives.